Implants placed in fresh extraction sockets in the maxilla: clinical and radiographic outcomes from a 3-year follow-up examination - Sanz, Mariano; Cecchinato, Denis; Ferrus, Jorge; Salvi, Giovanni E.; Ramseier, Christoph; Lang, Niklaus P.; Lindhe, Jan (Clinical oral implants research, 2014)
Aim The aim of this prospective, randomized, controlled multicenter study was to determine the 3‐year efficacy and stability of the soft and hard tissues at implants with a different geometry that were placed in fresh extraction sockets. Material and methods Implants with two different configurations, cylindrical (Group A) or conical/cylindrical (Group B) were installed, and healing abutments were attached. Sixteen weeks after implant placement, subjects returned for a re‐entry procedure. Prosthetic restorations were delivered 22 weeks after implant placement. Each subject was placed in a 3‐year follow‐up program, including examinations at yearly visits including various soft tissue and bone level parameters. Results The percentage of sites that were considered inflamed during the follow‐up period was stable and varied between 8.8% and 10.2%. The radiographic examinations documented improved bone levels at the final examination and the mean improvement from baseline (placement of permanent restoration; PR) amounted to 0.17 ± 0.67 mm. More than 70% (54 of 76) of the implants monitored in this study suffered no bone loss during the maintenance period. Moreover, there was an obvious “gain” of interproximal soft tissue volume and at the 3‐year examination around 25% of all embrasure gaps were completely filled with “papillae”. Conclusions Both conical/cylindrical and cylindrical implants placed in fresh extraction sockets allowed proper soft and hard tissue healing to occur. At both types of implants, mucosal inflammation was infrequent, marginal bone levels were maintained, and soft tissue volume increased gradually after the placement of the permanent restoration.